Participação do Estado Contrátil e do Relaxamento Miocárdico na Disfunção Ventricular durante a Transição Hipertrofia-Falência Cardíaca - Cicogna, Antonio Carlos [UNESP] (1997)
Purpose - To investigate the participation of contractile state and relaxation in cardiac muscle dysfunction during the transition from stable hypertrophy to cardiac decompensation in aging spontaneously hypertensive rats (SHR). Methods - isolated left ventricular papillary muscle function was studied in SHR with heart failure (SHR-F), in age-matched SHR without evidence of heart failure (SHR-NF), and in nonhypertensive controls Wistar-Kyoto rats (WKY). Muscles were analised in isometric and isotonic contractions in Krebs-Henseleit solution with calcium concentration of 1.25mM at 28°C. Results - Papillary muscles from SHR-F and SHR-NF demonstrated decreased active tension development and shortening velocity relative to normotensive WKY (p<0.05). SHR-F and SHR-NF did not differ. Compared with SHR-NF and WKY, muscle passive stiffness was increased in the failing SHR (p<0.05 versus WKY and SHR-NF). This parameter did not differ between SHR-NF and WKY (p> 0.05). Conclusion - These data suggest that the progression from stable hypertrophy to heart failure is associated with changes in the passive stiffness and is not related to depression of myocardial contractile function.